Gendered perspectives of ecosystem services: A systematic review - Yang, Y.C. Ethan; Passarelli, Simone; Lovell, Robin J.; Ringler, Claudia (Elsevier, 2018)
Women and men often have differential access to and derive different benefits from ecosystem services; therefore, their perception and knowledge of ecosystem services also differ. Understanding these differences is critical to ensuring that policies aimed at enhancing access to and use of ecosystem services can provide benefits to all genders. We conducted a systematic review of studies that aim to understand the relationship between gender and ecosystem service perceptions to summarize research from this emerging topic and to identify patterns between gender and ecosystem service perceptions from different case studies. The results show that highly gendered ecosystem services include medicinal products from forest or mangrove ecosystems and freshwater supply. Women have a stronger perception of water quality and erosion control, soil formation, habitat conservation and sustaining biodiversity. Men, on the other hand, had more knowledge of fuel and timber and extreme event mitigation services. Our review also identifies the limitations of sample size for this interdisciplinary topic, calls for more case studies and comparative studies to identify relationships between gender and ecosystem service perceptions, and calls for the development of models on ecosystem services that incorporate gender. Finally, we discuss how our review can augment existing gender frameworks for policymaking.